(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Road traffic accidents (RTAs) are a major public health concern, particularly among young adults. Despite increasing awareness, unsafe driving practices remain prevalent. This study assessed the knowledge, attitude, and practices (KAP) regarding road safety and their determinants among medical students in Perambalur district, Tamil Nadu. Materials and Methods: An institution-based cross-sectional study was conducted among 507 MBBS students using stratified random sampling. Data were collected through a pre-tested, validated questionnaire assessing sociodemographic characteristics and KAP on road safety. Descriptive statistics were used to summarize the data. Associations were analyzed using Chi-square tests, and independent predictors were identified using binary logistic regression. A p-value <0.05 was considered statistically significant. Results: The mean age of participants was 21.4 ± 1.7 years, with females comprising 67.7%. Adequate knowledge was observed in 48.5% of participants, while 72.4% demonstrated a positive attitude, and 59.2% exhibited good practices. Gender, year of study, driving experience, and method of learning to drive were significantly associated with all domains (p <0.05). Male gender was associated with higher odds of good knowledge (AOR = 1.72), positive attitude (AOR = 1.69), and good practice (AOR = 1.64). Driving experience >1 year (AOR = 4.12) and formal training (AOR = 2.15) were strong predictors of good practices. Conclusion: Although attitudes toward road safety were favorable, gaps persist in knowledge and practices. Experience and structured training play a key role in promoting safe behaviors, highlighting the need for targeted interventions.